ANALYSIS OF EARLY DETECTION, MOTIVATION AND WORK COMPETENCE ON THE QUALITY OF WORK RESULTS WITH INTERNAL CONTROL AS AN INTERVENING VARIABLE USING STRUCTURAL EQUATION MODELLING - Buang, Andri (LPPM Universitas Bina Bangsa, 2024)
The purpose of this study is to see the direct and indirect influence of early detection variables, motivation and work competence on the quality of work results. For indirect influence, the intervening variable used is internal control. The population used in this study is the State Civil Apparatus in eight Regional Apparatus Organizations of the Riau Islands Provincial Government. The sampling technique uses the total sampling technique. The analysis method used in this study is Structural Equation Modeling (SEM). The instrument to collect data in this study is a questionnaire using a Likert scale. The results showed that the variables of early detection, motivation and work competence did not have a significant effect on the quality of work results directly. For indirect effect, early detection, motivation and work competence have a significant effect on the quality of work results with internal control as an intervening variable.